Mediating Role of Open Innovation Between the Relationship of Blue Ocean Strategy and Innovation Performance, a Study of Malaysian Industry - Shafiq, Muhammad; Tasmin, Rosmaini; Takala, Josu; Imran Qureshi, Muhammad; Rashid, Mehwish (International Journal of Engineering and Technology, 2018)
This paper presents the introduction, literature review and methodology part of a bigger research work. Blue ocean strategy, open innovation strategy and innovation performance are the main constructs of this study. In the start after the introduction of problem of innovation performance and discussion of Malaysian industries specifically, Government linked companies is presented. Then variables of the study are discussed in detail. Then relationship of these variables are discussed, and the mediating variable of innovation strategy is presented. Relationship of these different variables are established from previous literature. In the end, theoretical framework is displayed and hypothesis are created for this study. Methodology and conclusion are also discussed. A self-administered questionnaire for Kim & Mauborgne’s Blue ocean strategy’s five characteristics is developed. While already established questionnaires are used for other two variables of innovation strategy and innovation performance. Results and discussion section presents the reliability, correlation and regression analysis of the pilot study, performed in Malaysian industry. In the end, possible future work of the study is elaborated.